Geodetic monitoring of the subsidence of a multi-storey building foundation - Gera, Oksana; Oleskiv, Roksolana; Dorosh, Liubov; Hrynishak, Mykola; Mykhailyshyn, Volodymyr (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
The presented study is devoted to determining the stability of the foundation of a seven-storey building located in Ivano-Frankivsk (Ukraine). A programme of surveying works was developed, taking into account its condition and configuration features. The project algorithm included laying deformation marks in the building foundation, performing geodetic observations using the method of high-precision geometric levelling, and processing and interpreting the results. The article provides an analysis of changes in the elevations of the building's deformation marks based on data from five series of observations carried out between 09/2019 and 06/2024. The results obtained indicate uneven subsidence of the foundation around the perimeter of the building, which led to the appearance of cracks.